PENGUKURAN KUALITAS JASA PELAYANAN KB MANDIRI DI PROVINSI ACEH - Zulkifli Zulkifli; Amri Amri; Eddy Munawar; Anwar Anwar (Faculty of Islamic Economics and Business, IAIN Lhokseumawe, 2019)
This study aims to measure the quality of family planning services in the province of Aceh which can later be useful for BKKBN policy in the context of determining the policy of providing unpaid contraception. The location of the study is Bireuen district and North Aceh district as regency areas with the highest number of active family planning participants according to the contraceptive method in the Private Service Line in March 2018. The number of samples used were 75 fertile age couples (PUS) obtained through the Multistage purposive sampling method followed by the snowball sampling method. Data were analyzed using Importance Performance Analysis (IPA) and Cartesian Diagrams. The results obtained are that all indicators measured show a high level of satisfaction on Mandiri (paid) KB services so it is recommended that the BKKBN can improve free KB services or otherwise prepare alternatives to stop free KB services.